(untitled) (Sustainability in Debate, 2022)
The process of institutionalizing deforestation control policies in the Brazilian Amazon has gone backwards in recent years. This article analyzes the trajectory of these policies between 1999 and 2020, with the dual aims of understanding how and why the State’s regulatory capacity has increased and explaining the dismantling of instruments and implementation capacity. This research is based on both qualitative and quantitative approaches, taking deforestation rates as a reference point and compiling the main forestry regulations at the national level in a timeline that covers the rise and fall of these policies. The conclusions show that between 1999 and 2012, the institutional trajectory of national policies and instruments on land use change followed a capacity-building pattern through the consolidation of policies and regulations. However, this pattern went into reverse from 2013 onwards. The period from 2019 has witnessed a process of active policy dismantling, culminating in a new surge in deforestation as well as a notable reduction in forest policy density, which has resulted in important land use changes that may cause irreversible damage to the rainforest and the ecological services it provides.